Anthropometric characteristics of Columbia, South Carolina, youth baseball players and Dixie Youth World Series players - French, K. E.; Spurgeon, J. H.; Nevett, M. E. (Research Quarterly for Exercise and Sport, 2007)
The purpose of this study was to compare measures of body size in two samples of youth baseball players with normative data from the United States National Center for Health Statistics (NCHS) growth charts. One sample of youth baseball players participated in a local little league. The second sample of youth baseball players were members of eight of the twelve teams participating in the 1995 Dixie Youth World Series. Normative data for the United States (NCHS) were used as comparative data. Two trained anthropometrists measured standing height, sitting height, lower limb height, upper limb length, arm girth, calf girth, tricep skinfold, and abdomen skinfold on all participants. In both samples, pitchers, short stops, and first basemen were a more highly skilled group and exhibited larger body size (greater standing height, sitting height, lower limb height, upper limb length) than children who played at other positions. The standing height of local little league players was similar to the median of reference data at ages 7, 8, and 9 years. The standing height and weight of skilled players in both samples approximated the 75th percentile for standing height and weight at ages 10, 11, 12, and 13 years. The results suggest that baseball players exhibit larger body size than the normal population at young ages. Body size may be an importantant criterion used by coaches to select and assign young players to certain positions.